The Morphology of Pollen Grains of Some Cultivars Rubus fruticosus L. - Motyleva, Svetlana Mikhailovna; Gruner, Lidia; Semenova, Larisa (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The features of pollen grains sculpture of 8 cultivars Rubus fruticosus L. have been studied in details via the scanning electron microscope method. The pollen material picked up in the Central region of Russia and the Republic of Adygeya has been used in the research. The comparative data of morphometric factors are presented, the polymorphism of pollen grains – size and surface is determined. The complex sculptural types are formed by the different combination of 2 or 3 simple sculptural types. The complex structural type of exine is characteristic of the studied cultivars Rubus fruticosus. The average size of pollen grains polar axis is within 32.43–37.46 µm; the equatorial diameter is within 16.91–18.88 µm. The ratio of polar and equatorial axis (Р/Е) marks the degree of the pollen grains elongation (roundness). The research showed that the cultivation region gives a certain influence on the change of the pollen average dimensions, but it does not influence P/E ratio. The pollen grains form is oblong-ellipsoid. In the polar outline the grains are round. The pollen grains of the presented blackberry cultivars are 3- or 4-colporate, the apertures are long. The sculpture of the pollen grain exine is complex, it belongs to the two component sculptural type – rugulose, the picture has the species features. The morphometric and sculptural identical characteristics are separated: the form (the pollen grains elongation degree), the dimensions (the ratio of the polar axis to the equatorial axis (P/E), the number of apertures and the surface picture (microstructure).